Ekspert i jego obecność w dyskursie poświęconym COVID-19 (na podstawie materiału telewizyjnego) - Rybka, Małgorzata; Wrześniewska-Pietrzak, Marta (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2025)
The aim of the article is to reconstruct the image of an expert presented in television discourse during the SARS-CoV-2 pandemic. The analysis focuses on the main editions of news broadcasts: Wiadomości (TVP1), Wydarzenia (Polsat), Fakty (TVN). They were broadcast from March 4, 2020 to July 12, 2020, i.e. from the first case to the second round of the presidential election in Poland. The material for the analysis consists of the news programs, which were excerpted based on the encoded material developed within the project “COVID-19 – the Black Series Continues” funded by the COVID- 19 Research competition of Adam Mickiewicz University in Poznań [Rybka, Wrześniewska-Pietrzak, Wiatrowski, Zagórska, Kołodziejczak, Świerkowska, Wyszyński 2021]. The selected news pieces included those featuring an expert. Qualitative and quantitative analyses of these broadcasts revealed the frequency of appearances of various experts and the diverse profiles of this concept in the analyzed news programs. This diversity stems from the fact that during the pandemic, television news programs featured experts who were not always specialists in the medical field. However, their words, used for persuasive purposes, allowed the authority of the expert to influence not only social moods but also the attitudes and actions taken by citizens.